2019
DOI: 10.1121/1.5101884
|View full text |Cite
|
Sign up to set email alerts
|

Sound quality metric indicators of rotorcraft noise annoyance using multilevel regression analysis

Abstract: It is hypothesized that sound quality metrics, particularly loudness, sharpness, tonality, impulsiveness, fluctuation strength, and roughness, could all be possible indicators of the reported annoyance to helicopter noise. To test this hypothesis, a psychoacoustic test was recently conducted in which subjects rated their annoyance levels to synthesized helicopter sounds [Krishnamurthy, InterNoise2018, Paper 1338]. After controlling for loudness, linear regression identified sharpness and tonality as important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Tonality is a metric aimed at identifying and quantifying the perceptual effects of tonal components in a given sound. Sharpness, tonality and fluctuation strength have been found well correlated with rotorcraft noise annoyance [ 30 , 31 ]. In a study investigating the noise annoyance of hovering UAVs, Gwak et al [ 14 ] found that the noise annoyance of UAVs (with MTOM ranging from 113.5 g to 11 kg) was highly related to loudness, sharpness and fluctuation strength.…”
Section: Regulation and Metricsmentioning
confidence: 99%
“…Tonality is a metric aimed at identifying and quantifying the perceptual effects of tonal components in a given sound. Sharpness, tonality and fluctuation strength have been found well correlated with rotorcraft noise annoyance [ 30 , 31 ]. In a study investigating the noise annoyance of hovering UAVs, Gwak et al [ 14 ] found that the noise annoyance of UAVs (with MTOM ranging from 113.5 g to 11 kg) was highly related to loudness, sharpness and fluctuation strength.…”
Section: Regulation and Metricsmentioning
confidence: 99%
“…LAeq, drone noise source and visual scene, on the reported loudness, annoyance and pleasantness was evaluated using a "one-off" approach. In this approach, the importance of each factor is assessed based on model accuracy when removing it from the analysis (Boucher et al, 2019). Three multilevel linear regression models were tested, M1 (fixed intercept, fixed slopes), M2 (fixed intercept, variable slopes) and M3…”
Section: Importance Of Acoustics and Non-acoustics Factors Of Drone Nmentioning
confidence: 99%
“…Stage 3 consists of a multilevel linear regression analysis, to identify the significance of subjectdependent responses of perceived annoyance. Multilevel linear regression has been used previously to investigate the factors contributing to annoyance for rotorcraft and small UAV, and has found to be a useful tool in discovering key variables [4] [7]. Multilevel linear regression is a method that integrates no pooling and complete pooling of data between subjects.…”
Section: Discussionmentioning
confidence: 99%
“…𝛾 𝑛0 , which does not vary per subject, is the regression coefficient of the 𝑛-th SQM 5 th percentile value of sound 𝑖. Furthermore, introducing subject-dependent regression slope coefficients for each SQM can reveal more information about the variance between how participants perceive these metrics, but previous literature has found that introducing subject-dependent slopes for this style of SQM analysis yielded little improvement to model accuracy when compared to the increase in accuracy introduced by including subject-dependent intercepts [7]. Therefore, a subject-dependent slope and intercept model was omitted from this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation